Recent advances in biological properties of brown algae-derived compounds for nutraceutical applications - Silva, Aurora (2022)
The increasing demand for nutraceuticals in the circular economy era has driven the research toward studying bioactive compounds from renewable underexploited resources. In this regard, the exploration of brown algae has shown significant growth and maintains a great promise for the future. One possible explanation could be that brown algae are rich sources of nutritional compounds (polyunsaturated fatty acids, fiber, proteins, minerals, and vitamins) and unique metabolic compounds (phlorotannins, fucoxanthin, fucoidan) with promising biological activities that make them good candidates for nutraceutical applications with increased value-added. In this review, a deep description of bioactive compounds from brown algae is presented. In addition, recent advances in biological activities ascribed to these compounds through in vitro and in vivo assays are pointed out. Delivery strategies to overcome some drawbacks related to the direct application of algae-derived compounds (low solubility, thermal instability, bioavailability, unpleasant organoleptic properties) are also reviewed. Finally, current commercial and legal statuses of ingredients from brown algae are presented, considering future therapeutical and market perspectives as nutraceuticals.